2015
DOI: 10.1134/s1022795415030084
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors in developmental genetics and the evolution of higher plants

Abstract: Transcription factors play an essential role in controlling various developmental programs in plants, coordinating the action of any genetic network. Among the most important groups of plant transcrip tion factors are the homeodomain containing transcription factors, in particular, those belonging to the KNOX and WOX families, the functions of which are associated with regulation of the meristem activity, development of the aboveground and underground parts of plants, and control of embryogenesis. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 123 publications
1
11
0
Order By: Relevance
“…The WOX5 gene is the central regulator of root apical meri-stem (Sarkar et al, 2007), and according to our data, it also regulates the development of symbiotic nodules in legumes (Osipova et al, 2012). Local analysis of the expression of these genes in the crop-roots and spontaneous tumors of radish lines using reporter constructs carrying the glucuronidase (GUS) showed different spatial expression patterns (Lebedeva et al, 2015;Lutova et al, 2015). Before the initiation of tumors, the expression of both genes takes place in the cambium -in the case of WOX5, it is confined to the part of cambium opposite the proto-xylem pole.…”
Section: Geneticssupporting
confidence: 55%
See 1 more Smart Citation
“…The WOX5 gene is the central regulator of root apical meri-stem (Sarkar et al, 2007), and according to our data, it also regulates the development of symbiotic nodules in legumes (Osipova et al, 2012). Local analysis of the expression of these genes in the crop-roots and spontaneous tumors of radish lines using reporter constructs carrying the glucuronidase (GUS) showed different spatial expression patterns (Lebedeva et al, 2015;Lutova et al, 2015). Before the initiation of tumors, the expression of both genes takes place in the cambium -in the case of WOX5, it is confined to the part of cambium opposite the proto-xylem pole.…”
Section: Geneticssupporting
confidence: 55%
“…The functions of TF KNOX are known to be associated with the control of cell proliferation mainly in shoot meristems (Tsuda and Hake, 2015), while TF WOX is necessary for maintaining stem cells in undifferentiated status (Dolzblasz et al, 2016). The literature describes in detail the role of TF KNOX and WOX in the development of the main plant meristems -the shoot and root apical meristem and also the lateral meristem cambium (reviewed in Lutova et al, 2015); in recent years, data have been obtained on the role of these TFs in the development of some types of irregular secondary meristem (Osipova et al, 2012;Azarakhsh et al, 2015).…”
Section: Geneticsmentioning
confidence: 99%
“…Transcription factors (TFs) play the central roles as drivers of gene expression in all living organisms since they control the rate of genetic transcription and coordinate the action of any genetic network [103,104]. The studies evidence that the various family of TFs are associated with the growth and development of the aboveground and underground parts of plants, abiotic stress responses, response to pathogens and many more [103,[105][106][107][108][109]. Thus, identification of the regulatory TFs of the reported RNAi genes can help to improve our understanding of gene silencing process in C. sinensis.…”
Section: Regulatory Relationship Between Tfs and Rnai Genesmentioning
confidence: 99%
“…Many studies have demonstrated that WUSCHEL-RELATED HOMEOBOX ( WOX ) transcription factors are involved in controlling the early stages of embryogenesis, the maintenance of meristem activity, and the formation of lateral organs, such as lateral roots, leaves, and floral primordia 1 , 2 . Moreover, it has been reported that the action of WOX s is regulated by CLE peptides (CLAVATA3/EMBRYO SURROUNDING REGION-RELATED) 3 and by the two major plant hormones: (1) auxins in the root apical meristem (RAM) and the cambium, and (2) cytokinins in the shoot apical meristem (SAM) 4 .…”
Section: Introductionmentioning
confidence: 99%